Loading and scheduling for flexible manufacturing systems with controllable processing times. Issue 3 (4th March 2019) - Zhou, Yi-Dong; Shin, Jeong-Hoon; Lee, Dong-Ho
ABSTRACT: This study addresses the problem of determining the allocation of operations and their tools to machines, the operation processing times and the allocation/sequence of the parts to be processed on each machine for flexible manufacturing systems with controllable processing times. Tool lives, tool copies and tool sharing are also considered. An integer programming model is developed for the objective of minimizing the sum of operation processing and tardiness costs. Then, iterative algorithms are proposed that solve the two subproblems iteratively, where the loading subproblem is solved by a modified bin packing algorithm under initial processing times and the resulting scheduling subproblem is solved by a priority scheduling method while modifying the loading plans and operation processing times iteratively. Computational experiments were carried out, and the results are reported.